Motoric Ability Survey in Kindergarten with Calligraphy Method - Irmawati Irmawati; Ibrahim Ibrahim (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2022)
The purpose of the study was to determine the level of fine motor skills at the age of five to six years. The population in this study were students in group B with a total of 55 students, group B1 with 28 students, and B2 with 22 students. The research design used a survey method. The data collection technique was carried out by testing the flexibility of hand movements and tests of eye and hand coordination. The results of the research show the percentages which include very well developed (BSB) 5%, category developing according to expectations (BSH) 20%, category starting to develop (MB) 40%, and category not yet developed (BB) 25%. Fine motor skills in group B1 with the percentage of BSB 4.35%, BSH 26.09%, MB 34.78%, and BB 26.09%. While the B2 group with a percentage of BSB 9.68%, BSH 25.81%, MB 32.26%, and BB 25.81. For this reason, the conclusions from the results of research at Pertiwi Kindergarten 26-13 Bogares Kidul in both groups to improve fine motor skills using the calligraphy method are said to be starting to develop.